Family with sequence similarity 13C (FAM13C) overexpression is an independent prognostic marker in prostate cancer - Burdelski, Christoph (Oncotarget, 2017)
FAM13C, a gene with unknown function is included in several mRNA signatures for prostate cancer aggressiveness. To understand the impact of FAM13C on prognosis and its relationship to molecularly defined subsets, we analyzed FAM13C expression by immunohistochemistry on a tissue microarray containing 12,400 prostate cancer specimens. Results were compared to phenotype, ERG status, genomic deletions of 3p, 5q, 6q and PTEN, and biochemical recurrence. FAM13C was detectable in cell nuclei of cancerous and non-neoplastic prostate cells. 67.5% of 9,633 interpretable cancers showed FAM13C expression: strong in 28.3%, moderate in 24.6% and weak in 14.6%. Strong FAM13C expression was linked to advanced pT stage, high Gleason grade, positive lymph node status, and early biochemical recurrence (p < 0.0001 each). FAM13C expression was associated with TMPRSS2:ERG fusions. It was present in 85% of ERG positive but in only 54% of ERG negative cancers (p < 0.0001), and in 91.1% of PTEN deleted but in only 69.2% of PTEN non-deleted cancers (p < 0.0001). The prognostic role of FAM13C expression was independent of classical and quantitative Gleason grade, pT stage, pN stage, surgical margin status and preoperative PSA. In conclusion, the results of our study demonstrate that expression of FAM13C is an independent prognostic marker in prostate cancer. Finding FAM13C also in non-neoplastic prostate tissues highlights the importance of properly selecting cancer-rich areas for RNA-based FAM13C expression analysis.